FUNGSI DAN PERANAN BADAN PENANAMAN MODAL DAN PROMOSI DAERAH PROVINSI RIAU - Ade Christhina; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Investment and Promotion Agency Region (BPMPD) Riau province is a non-departmental body directly responsible to the Governor. Investment and Promotion Agency Region (BPMPD) Riau province is a body that deals with investments both foreign investors and domestic. Investment and Promotion Agency Region (BPMPD) in charge of promoting regional potential and investment opportunities Riau, facilitate and enhance the development of investment cooperation, perform data collection, monitoring, evaluation and implementation of investment development, make efforts to the development and refinement of increased promotion and investment potential of the region, increase quality investment administration.Keywords: Investment and Promotion Area (BPMPD), Riau Province, Investors